The philosophy of mathematical practice - Mancosu, Paolo (Oxford : Oxford University Press, 2008)
This title offers philosophical analyses of important characteristics of contemporary mathematics and of many aspects of mathematical activity which escape purely formal logical treatment.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Mathematical analysis -- Foundations